USM INSTILS THE SPIRIT OF HUMANITARIAN - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, June 2016 Universiti Sains Malaysia (USM) has always strive to educate and instill in its community a strong spirit of humanitarian to go alongside its efforts to develop the knowledge of Science and Technology.